Pendekatan Interdispliner Dalam Studi Islam: Pengembangan Paradigma Integratif-Interkonektif Tradisi Ngebuyu Di Lampung Dalam Perspektif Islam - Agus Mardianto; Muhammad Samsul Hidayat; Yani Hartati; Muhammad Syaifullah (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to develop an integrative-interconnective paradigm of the ngebuyu tradition of giving birth to a baby in Lampung from an Islamic perspective. The ngebuyu tradition is a Lampung traditional ritual carried out after the birth of a baby. This tradition has noble values that can be integrated with Islamic teachings. This research was carried out using the library research method, namely collecting and analyzing data from various library sources. The research results show that the ngebuyu tradition has several values that are in line with Islamic teachings, such as the values of gratitude, mutual cooperation and solidarity. These values can be integrated with Islamic teachings through an integrative-interconnective paradigm. This paradigm emphasizes the importance of connecting tradition and religion, so that both can strengthen and enrich each other.